Fantasy vs. Reality: the Creation of Parallel Worlds in Fiction Case Study: The Magus 1977 by John Fowles - Khatoui ,Noureddine; Remmache, Sarah; Bakhouche, Salah (Faculty of Letters and Foreign Languages Department of English, 2019)
This dissertation studies how humans created parallel worlds to escape the hardships of their existence. It describes the writer’s implementation of these worlds and the interplay between reality and fantasy seeking to shed light on the relationship between the fictional worlds and the actual world. Therefore, it hypothesises that fictional worlds are imaginative constructs which are necessary to ground for alternative realities. Thus, the current research undertakes a descriptive analytical approach to study the analogy between fantasy and reality and how the created parallel worlds in fiction resulted in complicating the concept of reality. It employed the possible worlds’ theory to analyse JohnFowles’ novel The Magus as it presents the multi-faceted reality which characterises the contemporary world. From this study, we conclude that the Magus is effectively one of the stories that indicated through mystery the complexities of the external world which remains hard for the individual to understand since it makes the essence of life itself always shrouded in vagueness